IMPLEMENTASI METODE EXPONENTIAL SMOOTHING UNTUK PERAMALAN KEDATANGAN WISATAWAN MANCANEGARA PADA PULAU BALI - Nafis Sulthan; Nurafni Eltivia; Nur Indah Riwajanti (Media Mahardhika, 2020)
The purpose of this study is to predict the arrival of foreign tourists on the island of Bali by using the Exponential Smoothing method. This research is a quantitative descriptive. The data used in the study are data on foreign tourist arrivals from the air and sea routes taken from the Central Statistics Agency. Data is managed through the Microsoft Excel application. In determining the RMSE, the Solver Parameters help listed in Microsoft Excel is used to determine the lowest error rate. The data used in this study indicate that there are trend and seasonal patterns so that the most suitable Exponential Smoothing method is the Triple Exponential Smoothing method. The results of this study indicate that foreign tourist arrivals on the island of Bali are predicted to increase in 2020 although not too significant. The results of this study are expected to help the Bali Island government and related agencies in terms of planning and decision making to overcome the crisis on the island of Bali caused by the tourism sector.